Transparency and collateral: Central versus bilateral clearing - Gaetano Antinolfi; Francesca Carapella; Francesco Carli (Theoretical Economics, 2022)
This paper studies the optimal clearing arrangement for bilateral financial contracts in which an assessment of counterparty credit risk is crucial for efficiency. The economy is populated by borrowers and lenders. Borrowers are subject to limited commitment and hold private information about the severity of such lack of commitment. Lenders can acquire information, at a cost, about the commitment of their borrowers, which affects the assessment of counterparty risk. Clearing through a central counterparty allows lenders to mutualize counterparty credit risk, but this insurance may weaken incentives to acquire and reveal information. If information acquisition is incentive-compatible, then lenders choose central clearing. If it is not, they may prefer bilateral clearing either to prevent strategic default or to optimize the allocation of costly collateral.
Keywords: G10; G14; G20; G23; 330; Limited commitment; central counterparties; collateral